Vampire Motif in O. Mirtov’s Novel Dead Swell: Gender Aspect - Ekaterina V. Kuznetsova (Studia Litterarum, 2024)
The article discusses the reinterpretation in O. Mirtov’s (Olga Negreskul) novel Dead Swell (1909) of the images and plot moves of the novel by English writer Bram Stoker Dracula (1897) and, in general, the vampiric myth peculiar to romantic and neo-Gothic literature. Recognizable clichés associated with the appearance and abilities of vampires manifest themselves at different levels of the novel: at the level of subtext in ambiguous conversations about blood, in the description of the appearance of the characters (red lips, a string of red coral beads around the neck, pallor, haggardness), in the characteristics of their actions (the physical attraction of a man to a woman is compared with the craving of a vampire to fresh blood, it is realized in the form of sadistic pleasure associated with violence: forced intimacy, neck bites, beatings, tickling). These artistic details form a cross-cutting motif of vampirism. The writer’s appeal to the vampiric myth is due to the gender issues of the novel Dead Swell. The reader reveals the picture of psychological and sexual vampirism and the eternal conflict between man and woman in an androcentric society. In this struggle of the sexes, a woman, as a rule, finds herself in the role of the defeated and most often dies, and her tormentor, like a vampire, goes in search of the next victim. With the help of the motif of vampirism, Negrescul reveals and comprehends from the point of view of a woman the taboo themes of violence, sex, and death in Russian classical literature, which allows her to express her attitude to the “women’s question,” “the problem of gender,” the concepts of eros and platonic love.